Introducing marketing - Burnett, John, 1944-; BC Open Textbook Project; BCcampus (Global Text, 2011)
"Through good economic times and bad, marketing remains the pivotal function in any business. Determining and satisfying the needs of customers through products that have value and accessibility and whose features are clearly communicated is the general purpose of any business. It is also a fundamental definition of marketing. This text introduces students to the marketing strategies and tools that practitioners use to market their products."--BCcampus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on version viewed on BCcampus OpenEd website; title from pdf title page.
Keywords: Marketing -- Textbooks; Electronic books